Plato Images, Aims, and Practices of Education - Mintz, Avi I. (SpringerBriefs on Key Thinkers in Education,, 2018)
This book opens by providing the historical context of Plato's engagement with education, including an overview of Plato's life as student and educator. The author organizes his discussion of education in the Platonic Corpus around Plato's images, both the familiar - the cave, the gadfly, the torpedo fish, and the midwife - and the less familiar - the intellectual aviary, the wax tablet, and the kindled fire. These educational images reveal that, for Plato, philosophizing is inextricably linked to learning; that is, philosophy is fundamentally an educational endeavor. The book concludes by exploring Plato's legacy in education, discussing the use of the "Socratic method" in schools and the Academy's foundational place in the history of higher education. The characters in Plato's dialogues often debate - sometimes with great passion - the purpose of education and the nature of learning. The claims about education in the Platonic corpus are so provocative, nuanced, insightful, and controversial that educational philosophers have reckoned with them for millennia. .